Relationship of Mutation of Codon S 315 T KatG Mycobacterium Tuberculosis Gene with The Incidence of Multidrug Resistance Tuberculosis in South Sumatra - Diah Syafriani; Rouly Pola Pasaribu; Zen Ahmad; Erial Bahar (Biomedical Journal of Indonesia, 2020)
MDR TB is the condition of M. tuberculosis (Mtb) that is resistant to at least isoniazid (INH) and rifampisin. This condition caused by certain genomic mutation in some Mtb spesific gene. Some gene that had role in INH mutation are katG, inhA, ahpC, ndh and kasA gene. The most common gene that mutates is katG gene, around 50-80 %, and the most mutation(64%) found in codon S 315T. Aim to know the correlation between Mtb codon S 315 T katG gene mutation and prevalence of multidrug resistance tuberculosis in South Sumatera This observational study with cross sectional approach was conducted in RSMH Palembang collaborated with Clinical Microbiology Laboratory Faculty of Medicine Universiats Sriwijaya from January to July 2019. The MDR TB group was 50 subjects the drug sensitive TB group was 21 subjects. Mtb katG codon S 315 T gene was isolated from each subjects using the PCR-RFLP method with the Mspl enzyme. KatG codon S 315 T gene in this study was visualized in 40 subjects only 26 subjects of MDR TB and 14 subjects of drug sensitive TB group. Result the frequency distribution genetic of MDR TB group was 65.38% wildtype and 34.62% mutant; in drug sensitive TB group was 92.86% wildtype and 7.14% mutant. The codon S 315 T katG gene mutation in this study was not correlated with the incidence of MDR TB (p = 0.07, OR = 6.8 (0.77 - 61.40, 95% CI)).Conclusion the codon S 315 T katG Mtb gene mutation was found in 34,62% subjects, but not significantly related to the incidence of MDR TB in South Sumatra.